2006
DOI: 10.1039/b603961h
|View full text |Cite
|
Sign up to set email alerts
|

A novel miniature cell retainer for correlative high-content analysis of individual untethered non-adherent cells

Abstract: The importance of research involving non-adherent cell lines, primary cells and blood cells is generally undisputed. However, the task of investigating the complexity and heterogeneity of these cells calls for their long-run monitoring at a single-cell resolution. Such a capability is currently unavailable without having to use disruptive cell tethering. The present Cell Retainer (CR) concept enables high-content correlative multi-parametric measurements, from the functional to molecular level, of the same liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 23 publications
1
83
0
Order By: Relevance
“…Cytomics is becoming increasingly important for analyzing cell conditions and cellular responses to stimuli from extracellular milieu, which will contribute to drug discovery as well as predictive medicine. Cell microarray-based analysis offers one way for analyzing cytomics; it has been conventionally performed with a single parameter (11)(12)(13)(14)(15)(16)(17)(18). Here, for the first time, we present a method of two-parameter cell microarray-based time-lapse analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytomics is becoming increasingly important for analyzing cell conditions and cellular responses to stimuli from extracellular milieu, which will contribute to drug discovery as well as predictive medicine. Cell microarray-based analysis offers one way for analyzing cytomics; it has been conventionally performed with a single parameter (11)(12)(13)(14)(15)(16)(17)(18). Here, for the first time, we present a method of two-parameter cell microarray-based time-lapse analysis.…”
Section: Resultsmentioning
confidence: 99%
“…After that, the MAC-CCD system detected the position of each microwell on the chip again. Fifteen seconds after the stimulation, the fluorescence images of the fluo-4 signals were acquired on the whole microwell area every 3 s for an additional 45 s (scanning points [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The cells inside the wells did not move out of the wells after four gentle washes.…”
Section: Mouse B-cell Preparation and Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Deutsch et al reported a live cell array to perform cell-based assays on thousands of individual cells (7). Microcavities were arrayed in a honeycomb-like structure and could monitor cell responses, such as reactive oxygen species generation, on a single-cell basis (23).…”
Section: Discussionmentioning
confidence: 99%
“…1a). 66,[71][72][73] These systems use computer-controlled, pneumatically driven systems to manipulate small quantities of fluids precisely through multiple modules. The utility of these systems for the detection and amplification of DNA or RNA from individual cells has been described.…”
Section: Microfluidic-based Cell Trap Technologiesmentioning
confidence: 99%